Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-38
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic boundaries in subordinate syntactic constructions

Abstract: Based on a video recording of conversational British English, this paper tests whether several different subordinate syntactic structures are evenly vocally integrated to their environment. "Secondary constructions" have been described in linguistics as dependent, subordinate forms elaborating on primary elements of discourse. Although their verbal and vocal characteristics have been deeply analysed, few studies have provided a qualified picture of their vocal integration. Beyond showing that secondary constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In particular, we find strong effects of subject/object function on prosodic features, most prominently pitch and duration. We also find highly significant differences between the functions of verbs in different types of clauses (similarly to [21]). While overall the effect sizes may seem small, most are well above the just noticeable differences for pitch [22] and tempo [23].…”
Section: Discussionmentioning
confidence: 67%
“…In particular, we find strong effects of subject/object function on prosodic features, most prominently pitch and duration. We also find highly significant differences between the functions of verbs in different types of clauses (similarly to [21]). While overall the effect sizes may seem small, most are well above the just noticeable differences for pitch [22] and tempo [23].…”
Section: Discussionmentioning
confidence: 67%
“…However, the significant presence of hand beats and eyebrow rises hint at the prevalent use of prosodic gestures in both types of subordinate constructions. Interestingly, in the vocal modality, rhythmic cues also play a seminal role in the demarcation of both constructions (Lelandais & Ferré, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout a vocal paragraph, pitch height naturally declines in a progressive manner. A subordinate unit is signalled by downward changes in key (i.e., major levels in a speaker's pitch range) or in pitch height (Lelandais & Ferré, 2016). Intonation can convey subordinating information that is not marked with verbal means.…”
Section: Prosodymentioning
confidence: 99%
See 1 more Smart Citation
“…Production studies on the prosodic characteristics of syntactic subordination in spontaneous speech have shown that subordinate constructions display different degrees of prosodic autonomy depending on their syntactic type [5]; [6]. This study focuses on adverbial clauses, appositive clauses, and restrictive relative clauses, as illustrated in examples (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%